Influence of sulphur level on yield, uptake and quality of soybean (Glycine max) under temperate conditions of Kashmir valley - NAJAR, G R; SINGH, S R; AKHTAR, F; HAKEEM, S A (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2004 and 2005 to study the influence of sulphur levels on yield, uptake and quality of soybean (Glycine max L. Merr) under temperate conditions of Kashmir valley. Increasing levels of sulphur significantly increased growth, nodulation, yield, uptake and quality of soybean up to the application of 30 kg S/ha but maximum growth, nodulation, yield and quality of soybean was recorded under 40 kg S/ha which was at par with 30 kg S/ha. Stover and grain yield of soybean increased in the tune of 66.0 and 53.4% over the control due to addition of 40 kg S/ha, respectively. Application of 40 kg S/ha recorded highest total N, P, K, S, Ca and Mg nutrients uptake by soybean over the rest of the treatments. However, highest sulphur-use efficiency and apparent sulphur recovery was recorded with 10 kg S/ha, followed by 20 kg S/ha. The maximum N: S, K: S, Ca: S and Mg: S ratio were recorded under control, whereas minimum with the application of 40 kg S/ha in stover and seed of soybean. The available S at harvest soil increased significantly with S level.